Middle managers strategizing practices and its effects on implementation: the moderating roles of relationship quality with top managers - Vaz, Samir Lófti (2019)
This study explores implementation performance that derives from the conjoined manifestation of two different set of practices which middle managers (MMs) employ while participating in strategy, namely, involving and influencing. It draws on the notion of strategy as being a system of social exchanges to suggest that relationship quality between top managers (TMs) and MMs has a twofold moderating effect on implementation performance, based on the type of strategizing practices that MMs exhibit. Empirical evidence from MMs in a large-size Telecommunications Company support the hypothesis of having higher implementation performance when both MMs practices of involving and influencing exist. It also shows that the relationship quality between TMs and MMs has a moderating effect on implementation performance that is positive for MMs practices of involving, but negative for MMs practices of influencing. These findings contribute to the MMs perspective on strategy and to the stream of strategy-as-practice research focused on implementation, thus offering concrete implications for organizations and managers who want to leverage their impacts for strategy outcomes.